Photoluminescent vitroceramic nanocrystals based on silica-stabilised zirconium, production method thereof and product based on the nanocrystals, for thermal barrier coatings (2020)
Photoluminescent vitroceramic nanocrystals based on silicastabilised zirconium; a method for producing same; and a product based on the nanocrystals, for thermal barrier coatings; a method for obtaining the nanocrystals and a product with photoluminescent properties and high-temperature structural stability, for thermal coatings.